Thermal Efficiency of On-site, Small-scale Hydrogen Production Technologies using Liquid Hydrocarbon Fuels in Comparison to Electrolysis: a Case Study in Norway. (August 2018) - Ravasio, Lucrezia; Ravelli, Silvia; Mustafa, Mohamad
Abstract: The main goal of this study was to assess the energy efficiency of a small-scale, on-site hydrogen production and dispensing plant for transport applications. The selected location was the city of Narvik, in northern Norway, where the hydrogen demand is expected to be 100 kg/day. The investigated technologies for on-site hydrogen generation, starting from common liquid fossil fuels, such as heavy naphtha and diesel, were based on steam reforming and partial oxidation. Water electrolysis derived by renewable energy was also included in the comparison. The overall thermal efficiency of the hydrogen station was computed including compression and miscellaneous power consumption.